Repeat Intrathecal Triamcinolone Acetonide Application Reduces Acute Occurring Painful Dysesthesia in Patients with Relapsing Remitting Multiple Sclerosis. (2006) - Hellwig, Kerstin; Lukas, Carsten; Brune, Niels; Hoffmann, Volker; Schimrigk, Sebastian; Przuntek, Horst; Müller, Thomas
Abstract : We describe four patients with relapsing remitting multiple sclerosis (RRMS) who experienced a relapse with acute onset of painful sensations. Pain sensations disappeared in two of them and markedly reduced in the other ones after repeat application of intrathecal triamcinolone acetonide (TCA) following a prior unsuccessful treatment with intravenous steroids. TCA administration was well tolerated and no serious side effects occurred. Repeated intrathecal TCA injection may provide a substantial benefit in RRMS patients with acute onset of pain due to an inflammatory lesion within the spinal cord.